Impact of health capital on productivity and economic growth in Singapore - Opeoluwa Isreal, Akingba Idowu (2017)
Emphases on health capital as a primary factor influencing economic growth and productivity dates back as early as 1780. For instance, Jeremy Bentham (1780) in his seminal work urged individuals to be more involved in activities encouraging wellness. According to Bentham, health is critical to development. He defines wellbeing (health) as the surfeit of pleasure over pain and distinguishes between health and ill health, which he associates with being destitute, poverty, unhappiness, diseases and hunger. Although, World Health Organization (WHO) (1948) defined health as "a state of complete physical, mental, and social well-being and not merely the absence of disease or infirmity, however, it was Grossman (1972) that initiated health capital concept. In his study, he sees health (a human capital stock) as both consumption and an investment good. Thus, both arrangement conceives health as a basic and key ingredient of human capital and an important determinant of economic growth and productivity. Despite widespread development in the discipline of health economics, there has been little or no references given to health capital as a determinant of economic growth or productivity in studies. On this ground, this study focused on Singapore, a country that has registered high GDP growth rate for three decades (1980 to 2010) with modest productivity growth rate and well recognized for its well-established and efficient health care system and healthcare financing, but no empirical studies has been conducted to show whether the vast improvement in the country health capital has any impact on the country miraculous growth. Thus, the study seeks to examine the impact of health capital on the productivity and economic growth in Singapore using autoregressive distributed lag model (ARDL) and error correction model (ECM) on data from 1980-2013. The first research objective is to examine the impact of health capital on productivity. The finding from bounds test indicates that there is stable long run cointegration between productivity, human capital (measured by education expenditure per capita), health capital (measured by health expenditure per capita) and domestic investment (measured by gross fixed capital formation). Thus, the evaluated long run model uncovers that health capital contributes positively and significantly to productivity in Singapore. The second research objective is to examine the impact of health capital on economic growth. Similarly, the findings demonstrate that there is a stable long run cointegration between GDP per capita, human capital (measured by education expenditure per capita), health capital (measured by health expenditure per capita), trade openness and gross domestic savings. The estimated long run model also reveals that health capital contributes positively to Singapore’s economic growth. The finding implies that Singapore’s productivity and economic growth could be improved significantly if expenditure on health capital is increased. This would have a substantial impact on human productivity which will further lead to improved output per capita in the long run.